The characterization of halophilic polyhydroxyalkanoate-producing bacteria from brine in Solivar near Prešov (Slovakia) - Adhvaryu, Shivani; Kiskova, Jana; Piknova, Maria; Malinicova, Lenka; Beck, Terezia; Buchtikova, Iva; Kourilova, Xenie; Kizovsky, Martin; Samek, Ota; Obruca, Stanislav; Pristas, Peter (World journal of microbiology & biotechnology, 2025)
The present study aims to isolate and investigate temporal variability of the halophilic and halotolerant microbiota present in brine from former salt mine Solivar, Prešov (Slovakia) especially with respect to with their ability to produce polyhydroxyalkanoates (PHA). Brine sampling was performed in the year 2020 and 2021 and samples were inoculated on the R2A medium with 5% NaCl for the bacterial isolation. We obtained a total of 53 halophilic isolates and one halotolerant isolate, all of which were tested for their ability to produce PHA via Nile Blue A staining, Raman spectroscopy and Gas chromatography. The low diverse halophilic microbiota was dominated by Proteobacteria members (mainly Halomonas, Halovibrio, and Chromohalobacter sp.) and some of these bacteria represent newly identified taxa. Around 80% of the isolates were able to produce PHA during growth on glucose-rich media, which highlights the importance of PHA for adaptation to high-salinity environments. Poly(3-hydroxybutyrate) (PHB) was the main type of PHA produced with the yield up to 2.76 g/L in Halovibrio sp. HP20-59. Overall, our investigation pointed out that brine from Solivar shows genetically variable community of halophilic bacteria most of which are capable of accumulation of PHA, hereby confirming the high biotechnological potential of halophilic bacteria.
Keywords: Salinity; salinita; Polyhydroxyalkanoates; Bacteria; soli; Microbiota; polyhydroxyalkanoáty; Halomonadaceae family; fylogeneze; PHA; RNA ribozomální 16S; Sodium Chloride; Raman spectroscopy; mikrobiota; Salts; chlorid sodný; hydroxybutyráty; Halophilic bacteria; RNA, Ribosomal, 16S; Phylogeny; Brine; Hydroxybutyrates